Distribuição temporal e espacial de haplótipos de Bemisia tabaci (Gennadius, 1889) no Brasil - Rizental, Muriel Santos (2020)
Bemisia tabaci is a polyphagous insect-pest that has been established in Brazil for almost 100 years ago. Efforts to map and identify variants of this species and host plants across Brazil have shown limited success due to the scarcity of samples from several states, including unique Brazilian biomes, and the lack of long-term collection, especially from the north and northeast regions. In this study, we analyzed new samples from the 26 states and the Federal District collected from 2014 to 2019 as well as a duplicate of the Embrapa Genetic Resources and Biotechnology museum collection from 1989 to 2005. The objectives were to identify the entry and environmental adaptation of haplotypes, map its distributions, and host plants in Brazil. The whiteflies´ samples were analyzed using mitochondrial DNA (mtDNA) cytochrome oxidase I (COI) and nuclear DNA (nDNA) (L11) genetic markers. Information and a nucleotides database were generated (~753 bp) for both collections. Interestingly, all the analyzed samples from the museum collection belonged to B-haplotype. The oldest sample was collected in 1989, in Rio de Janeiro (southeast region), and the second in 1990 in Ceará (northeast region). In the 2014-2019 collection, native A-haplotypes were identified in 12 Brazilian states. Invasive B-haplotype was identified throughout the country, except in Santa Catarina (southern region). The invasive Q-haplotype was detected in Alagoas, Maranhão, São Paulo, Paraná, and the Rio Grande do Sul. Three possible new host plants for B. tabaci were registered: A-haplotype on Acacia mangium (Acaciaceae) in Roraima (northern region); B-haplotype on Spondias mombin (Anacardiaceae) in Ceará; and Xanthosoma sagittifolium (Araceae) in Rio de Janeiro. These discoveries of new entry dates and locations of B-haplotype, as well as new host plants for native and invasive haplotypes and their dispersions in the country will have an impact on the management strategies for this pest in Brazil and the Americas.